DEMONSTRATION OF ANTIVIRAL ACTIVITY OF IVERMECTIN AGAINST R2B STRAIN OF NEWCASTLE DISEASE VIRUSINFECTED 9- DAY OLD CHICKEN EGGS 2 - T. Jagadeesh; G. Sathish; M. Parthiban; P. Raja; G. Sarathchandra (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Antiviral activity of ivermectin was examined against R2B strain of Newcastle disease virus in 9 - day old embryonated chicken eggs. Five distinct concentrations (500, 250, 100, 50, 10 µg/mL) of ivermectin were used in the study. Haemagglutination test was performed to determine the antiviral activity of ivermectin by using chicken RBC. The results revealed that ivermectin can exert a significant antiviral activity against Newcastle disease virus at higher concentrations (500, 250 and 100 µg/ml) but with cytotoxic effects. On the contrary a moderate to weak antiviral activity without cytotoxicity was demonstrated at lower concentrations (50, 10 µg/ml).